2011
DOI: 10.1371/journal.pone.0026200
|View full text |Cite
|
Sign up to set email alerts
|

Stretching Actin Filaments within Cells Enhances their Affinity for the Myosin II Motor Domain

Abstract: To test the hypothesis that the myosin II motor domain (S1) preferentially binds to specific subsets of actin filaments in vivo, we expressed GFP-fused S1 with mutations that enhanced its affinity for actin in Dictyostelium cells. Consistent with the hypothesis, the GFP-S1 mutants were localized along specific portions of the cell cortex. Comparison with rhodamine-phalloidin staining in fixed cells demonstrated that the GFP-S1 probes preferentially bound to actin filaments in the rear cortex and cleavage furro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 93 publications
4
135
0
Order By: Relevance
“…One possible mechanism for this is the preferential binding of myosin-II motor domains to mechanically stretched F-actin (Uyeda et al, 2011). Myo3 was hardly detectable on precursor medial reticular F-actin, whereas it accumulated along the sharp actin ring, which implies that the configuration or tension of the equatorial F-actin affects its affinity for Myo3.…”
Section: Discussion the Motor Properties Of Myo3 Are Relevant To Its mentioning
confidence: 99%
“…One possible mechanism for this is the preferential binding of myosin-II motor domains to mechanically stretched F-actin (Uyeda et al, 2011). Myo3 was hardly detectable on precursor medial reticular F-actin, whereas it accumulated along the sharp actin ring, which implies that the configuration or tension of the equatorial F-actin affects its affinity for Myo3.…”
Section: Discussion the Motor Properties Of Myo3 Are Relevant To Its mentioning
confidence: 99%
“…Thus, talin A appears to bind to cortical actin filaments that are interacting with myosin II. Uyeda et al (29) proposed that the head domain of myosin II preferentially binds to actin filaments stretched by interaction with myosin II and that this binding property of the head domain is responsible for the accumulation of myosin II itself in the posterior cortex of migrating cells and cleavage furrow of dividing cells. Washington and Knecht (30) reported that the actin-binding domains of filamin and α-actinin determine the distribution of the proteins, which show distinct, almost complementary localization patterns, suggesting that different actin-binding domains have different affinities for actin filaments in functionally distinct regions of the cytoskeleton.…”
Section: F) Migrating Talin A-null Cell Observed By Interference Reflmentioning
confidence: 99%
“…In mammalian nonmuscle myosin IIB, for example, when a myosin II head imposes a piconewtonrange resistive load on another, the second head releases ADP at a 10-fold slower rate than an unloaded head (0.023 5 0.003 s À1 vs. 0.27 5 0.06 s À1 ) (42). Second, in addition to inhibiting ADP release, force can trap the myosin II motor in the cooperative isometric state, which promotes the binding of additional myosin motors to the actin filament nearby due to a propagated conformational change in the actin filament (43)(44)(45). This cooperative binding state was specifically implicated in mechanosensitive accumulation by experiments in which the myosin II lever arm was lengthened or shortened (40).…”
Section: Chemical and Mechanical Inputs Direct Shape Changementioning
confidence: 99%